Screening for Syphilis During Pregnancy in Turkey - Yusuf Aytaç Tohma; Hasan Energin; Emel Ebru Özçimen; Eser Çolak (Medical Network, 2016)
OBJECTIVE: To assess the prevalence of syphilis among patients at a tertiary referral center in Turkey and determine the need for antenatal syphilis screening based on the results. STUDY DESIGN: A retrospective cohort study based on patient data obtained from a tertiary referral center in Turkey. Serological syphilis screening using the Venereal Disease Research Laboratory (VDRL) was performed on all pregnant women as a part of routine antenatal care at their first hospital visit during pregnancy. Treponema pallidum hemagglutination assay (TPHA) was used to confirm positive screening results for syphilis. RESULTS: Patients' mean age was 27.4 years. The incidence of positive syphilis serology was 0.013% (one patient), which was supported by a positive confirmatory test (0.013%).The TPHA-positive pregnant woman diagnosed with syphilis was treated with benzathine penicillin, and she gave birth to normal infants without any signs of congenital syphilis. CONCLUSION: Syphilis prevalence should be determined in each developing country with population-based studies. According to the prevalence of syphilis, each country should determine its own syphilis antenatal screening policies.